Pengaruh Problem Based Learning terhadap Minat Belajar IPAS Siswa Kelas IV SDN 67 Parepare - Usman; Ila Israwaty; Siti Hardianty (Lembaga Yasin AlSys, 2026)
Students’ low interest in learning Natural and Social Sciences (IPAS) is indicated by their lack of attention, interest, and active engagement during the learning process. This study aims to analyze the effect of the Problem-Based Learning (PBL) model on fourth-grade students’ learning interest in IPAS at UPTD SD Negeri 67 Parepare. The study employed a quantitative approach with a pre-experimental research type and a One-Group Pretest–Posttest design. The research sample consisted of 18 students from Grade IV.A who were selected using purposive sampling. Data were collected through a learning interest questionnaire administered before (pretest) and after (posttest) the implementation of the PBL model and were subsequently analyzed using descriptive and inferential statistics with the assistance of SPSS. The results showed that the students’ mean learning interest increased from 49.55 on the pretest to 87.83 on the posttest. The paired-samples t-test yielded a significance value of 0.001 (< 0.05); therefore, H₀ was rejected and H₁ was accepted. This study concludes that the PBL model has a significant effect on fourth-grade students’ learning interest in IPAS at UPTD SD Negeri 67 Parepare. These findings provide the practical implication that PBL can be used as an alternative instructional model to increase students’ attention, interest, and active engagement in IPAS learning at the elementary school level.